ENTEROBACTER SP. IN BALI CATTLE ACCORDING TO GEOGRAPHIC AND LEVEL OF MATURITY AND ITS SENSITIVITY PATTERNS TO ANTIBIOTICS - Suarnata, I Wayan; Suarjana, I Gusti Ketut; Tenden Rompis, Aida Louise (Buletin Veteriner Udayana; Vol. 10 No. 2 Agustus 2018DO - 10.24843/bulvet.2018.v10.i02.p08, 2018)
An observational study in order to determine the distribution Enterobacter sp in Bali cattle at different geographical area (highland and lowland) and according to the animal maturity (calves, heifers, adult) have been undertaken . Isolation and identification of bacteria based on the method of Carter and Cole with slightly modification and the antibiotic sensitivity test were determined using the disc diffusion method by Kirby and Bauer. The Enterobacter sp. was isolated from 16 (13.3%) out of the 120 nasal swab samples,where 8 (6.7%), 6(5.0%), and 2 (1.7%) was isolated from calf, heifers, and adults, respectively. Meanwhile, 6 (5.0%) Enterobacter sp. was isolated from the highland and the remains (8.3%) from the lowland. Antibiograms showed that 13 of the 16 isolates (81.2%) weresensitive to sulfamethoxazole and the remains (18.8%) intermediate. While 12 (75.0%), 1 (6.2%), and 3 (18.8%) isolates weresensitive, intermediate, and resistant to ampicillin, respectively. To oxytetracycline 8 (50.0%) isolates were sensitive, 4 (25.0%) isolates were intermediate, and 4 (25.0%) isolates were resistant. Generally, the Enterobacter sp isolates were sensitive to all the antibiotics tested.